The 1935 tax reform and the strengthening of direct taxation in Colombia (2014)
This paper explores the most relevant elements of tax reform proposed and implemented by President Alfonso López Pumarejo in 1935, during his first term of government. The reform was implemented fundamentally through Act 78 of 1935 and complemented by means of Act 63 of 1936. It is one of the important changes made during the period of the so-called “ongoing revolution”. One of the most relevant elements of the reform was the consolidation and strengthening of the direct taxes of Colombia using as principal instruments the increase of income tax and the creation of the taxes to the excess profits and estate tax. The new tax resources constituted an important source of financing of the comprehensive program of reforms and policies proposed by the government of President López.